1975
DOI: 10.2134/jeq1975.00472425000400020015x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Cadmium Accumulation of Plants Grown on a Soil Treated with a Cadmium‐Enriched Sewage Sludge

Abstract: Corn, wheat, rice, field bean, soybean, cabbage, spinach, lettuce, curlycress, carrot, turnip, radish, tomato, and squash plants were grown to commercial harvest stage using as the substrate, soil pre‐treated with a municipal sewage sludge (1%) containing variable amounts of CdSO4 up to 640 µg Cd/g soil. Observations included injury symptoms, yield decrement, Cd level of diagnostic tissue, and Cd and Zn content of harvested produce. Cadmium‐sensitive plants such as spinach, soybean, curlycress, and lettuce wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
7

Year Published

1979
1979
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(67 citation statements)
references
References 0 publications
3
57
0
7
Order By: Relevance
“…Soil studies on contaminated soils showed lettuce, spinach, celery and cabbage tended to accumulate relatively high concentrations of Cd, while potato tubers, corn, french beans and peas accumulated lower amounts of Cd (Davis and Carlton-Smith 1980). Spinach and lettuce also accumulated high Cd levels on soils with sludge application, while Cd concentrations were medium in radish and soybean and low in corn and rice (Bingham et al 1975). In sludge-treated soils, Cd concentration of tomato was higher than that of barley or beans (Bradford et al 1975).…”
Section: Factors Influencing CD Accumulation In Crops Plant Genetic Cmentioning
confidence: 97%
See 2 more Smart Citations
“…Soil studies on contaminated soils showed lettuce, spinach, celery and cabbage tended to accumulate relatively high concentrations of Cd, while potato tubers, corn, french beans and peas accumulated lower amounts of Cd (Davis and Carlton-Smith 1980). Spinach and lettuce also accumulated high Cd levels on soils with sludge application, while Cd concentrations were medium in radish and soybean and low in corn and rice (Bingham et al 1975). In sludge-treated soils, Cd concentration of tomato was higher than that of barley or beans (Bradford et al 1975).…”
Section: Factors Influencing CD Accumulation In Crops Plant Genetic Cmentioning
confidence: 97%
“…Cadmium accumulation and distribution in plants differ with species and among cultivars within a species (Page et al 1972;Bingham et al 1975;Pettersson 1977;Chang et al 1982;Kuboi et al 1986;Yang et al 1995). Cadmium concentration of plants grown in solution culture increased in the order: oats, wheat < bean, pea, sunflower, cucumber < corn, mustard < radish, kale, rape < tomato, carrot, sorrel < lettuce (Pettersson 1977).…”
Section: Factors Influencing CD Accumulation In Crops Plant Genetic Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Randall et al (1976) concluded that DTPA could be used successfully to determine the available Mn in low organic matter soil. Bingham et al (1975) showed a highly significant correlation between DTPA-extractable Cd and that taken up by corn. Singh and Narwal (1984) found numerically superior correlation coefficients between Cd, Pb and Zn extracted by DTPA and the total uptake of these metals by rape *The extractable trace elements (C E ) are expressed in percentage of the total content of the elements in the untreated soil and plant accumulation reduction of the elements in plant (⌬C P ) and in root (⌬C R ) are expressed in percentage of the total plant content of the elements in the untreated soil.…”
Section: Comparison Of Bi Among Different Extractantsmentioning
confidence: 95%
“…Metals' solubility changes reversely with soil pH, i.e., metal solubility increases with decrease in soil pH and, as a result, metal uptake by plants in calcareous soils is higher than plants in acidic soils (Fisseha 2002). Bingham et al (1975) found that Cd accumulation was lower in shoots of cereals and legumes than leafy vegetables such as curly cress, lettuce and spinach. All of these factors are very important to do further study in these fields.…”
Section: Physico-chemical Properties Of Textile Sludge and Pot Soilmentioning
confidence: 97%